Storybound - Burt, Marissa (New York : Harper, 2012)
Shy, twelve-year-old Una Fairchild is suddenly transported by a mysterious book into the Land of Story, where characters from books hope to be cast into a tale of their own, and Una attends the Perrault Academy while trying to discover why she is there.
Ages 8-12.
Keywords: Fantasy; Books and reading -- Fiction; Characters from literature -- Fiction; Adventure and adventurers -- Fiction; Books and reading -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Books and reading -- Fiction; Characters and characteristics in literature -- Fiction; Adventure fiction; Fantasy fiction; Adventure fiction; Fantasy fiction